An improved phase-shifted DPWM method for reducing switching loss and thermal balancing in cascaded H-bridge multilevel inverter - Kim, Seok Min; Lee, Eui Jae; Lee, June Seok; Lee, Kyo Beum (IEEE Access, 2020)
This paper proposes an improved discontinuous pulse-width modulation (DPWM) method based on phase-shifted PWM (PS-PWM) for three-phase cascaded H-bridge (CHB) multilevel inverters. Due to the CHB multilevel inverters employ a large number of power semiconductor switches, they suffer from device failures because the switches are one of the major failure factors in a power electronic system. Therefore, the reliability and life-time of CHB multilevel inverters are mainly determined by the reliability of switches. The most failure of switches is occurred by its accumulated thermal stress which is generated by power losses including the conduction and switching loss. By applying the conventional DPWM, the life-time of switches can be extended because it reduces the switching loss. The conventional DPWM, however, still operates with high speed carrier frequency and it is not enough to reduce the switching loss of the CHB multilevel inverter with a large number of inverter cells. The proposed novel DPWM method provides the improved switching loss reduction through the different switching behaviors for each leg. Additionally, the rotation scheme promises even power distribution and life-time management among inverter cells in a CHB multilevel inverter. The simulation results and experimental results confirm the switching loss reduction and even power distribution abilities of the proposed modulation method.
Keywords: Cascaded H bridge (CHB); Cascaded h-bridge multilevel inverters; Discontinuous pulse width modulations (DPWM); Multilevel inverter; Power distributions; Power electronic systems; Power semiconductor switches; Switching behaviors; Cascaded H-bridge multilevel inverter; Discontinuous pulse-width modulation; Power distribution; Power losses; Reliability of power conversion system